The PRaCTICaL study of nurse led, intensive care follow-up programmes for improving long term outcomes from critical illness: a pragmatic randomised controlled trial. (16th October 2009) - Cuthbertson, B H; Rattray, J; Campbell, M K; Gager, M; Roughton, S; Smith, A; Hull, A; Breeman, S; Norrie, J; Jenkinson, D; Hernández, R; Johnston, M; et al.
Abstract : Objectives To test the hypothesis that nurse led follow-up programmes are effective and cost effective in improving quality of life after discharge from intensive care. Design A pragmatic, non-blinded, multicentre, randomised controlled trial. Setting Three UK hospitals (two teaching hospitals and one district general hospital). Participants 286 patients aged ≥18 years were recruited after discharge from intensive care between September 2006 and October 2007. Intervention Nurse led intensive care follow-up programmes versus standard care. Main outcome measure(s) Health related quality of life (measured with the SF-36 questionnaire) at 12 months after randomisation. A cost effectiveness analysis was also performed. Results 286 patients were recruited and 192 completed one year follow-up. At 12 months, there was no evidence of a difference in the SF-36 physical component score (mean 42.0 (SD 10.6) v 40.8 (SD 11.9), effect size 1.1 (95% CI −1.9 to 4.2), P=0.46) or the SF-36 mental component score (effect size 0.4 (−3.0 to 3.7), P=0.83). There were no statistically significant differences in secondary outcomes or subgroup analyses. Follow-up programmes were significantly more costly than standard care and are unlikely to be considered cost effective. Conclusions A nurse led intensive care follow-up programme showed no evidence of being effective or cost effective in improving patients' quality of life in the year after discharge from intensive care. Further work should focus on the roles of early physical rehabilitation, delirium, cognitive dysfunction, and relatives in recovery from critical illness. Intensive care units should review their follow-up programmes in light of these results. Trial registration ISRCTN 24294750